Analisis Tingkat Kepuasan Kerja Karyawan pada Usaha Werdhi Guna Food di Desa Sibetan Kecamatan Bebandem Kabupaten Karangasem - SUPUTRA, I MADE; HANDAYANI, M.TH.; WULANDIRA SDJ, A.A.A. (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2016)
Abstract Employees are the main wealth for the company, because the human resources are the driving force of all available resources so that it can function properly in order to achieve corporate objectives that have been set. The purpose of this study to know employee’s job satisfaction rate effort Werdi Guna Food. The method of data analysis is descriptive method by using questionnaires, measured by using Likert’s Scale, namely to find out the rate of employee’s job satisfaction. The result of the research shows that the percentage rate of employee’s job satisfaction Werdi Guna Food reaches the score of 64.51%. Thus, the accomplishment of satisfaction rate for employees at the category of satisfied enough shows that most respondents feel satisfied enough as long as they work at Werdi Guna Food. Things which must have more attention to improve employee’s job satisfaction at Werdi Guna Food is satisfaction with salary and compensation received by employees, satisfaction to the attitude of their superior, satisfaction to award distribution , satisfaction to safety in working . Keywords : work satisfaction, employee, and likert scale